Spirocamallanus sindensis n. sp. from Catfish Rita rita (Siluriformes: Bagridae) of Pakistan: Spirocamallanus sindensis n. New Species from Pakistan (Biological Sciences - PJSIR, 2022)
The aimed of present studies to examination of helminth parasites of Indus river Siluriformes catfishes. 57 (41 + and 16 ) specimens were collected from 31 hosts fishes Rita rita (F. Hamilton, 1822) belong to genus Spirocamallanus (Baylis, 1923) processes as live specimen were killed in hot 70% ethanol, preserved, made temporary mounts for detail study. On the basis of differential characters such as body shape and size, striated cuticle format, buccal capsule shape and 13-14 spiral numbers, cephalic and cervical papillae, basal ring shape, spicules shape and size, vulva position and shape, vagina shape, the new species Spirocamallanus sindensis identified.